Metabolomics comparison of metabolites and functional pathways in the SH-SY5Y cell model of Parkinson's disease under PEMF exposure - Li-na Zhu; Deng Chen; Chengqi He (Heliyon, 2024)
Objective: PEMF is an emerging technique in the treatment of Parkinson's disease (PD) due to its potential improvement of movement speed. The aim of this study was to investigate the metabolic profiles of pulsed electromagnetic fields (PEMFs) in an SH-SY5Y cell model of PD. Methods: The SH-SY5Y cell model of PD was induced by 1-methyl-4-phenylpyridinium (MPP+). Liquid chromatography mass spectrometry (LC‒MS)-based untargeted metabolomics was performed to examine changes in the PD cell model with or without PEMF exposure. We conducted KEGG pathway enrichment analysis to explore the potentially related pathways of the differentially expressed metabolites. Results: A total of 275 metabolites were annotated, and 27 significantly different metabolites were found between the PEMF treatment and control groups (VIP >1, P < 0.05), mainly including 4 amino acids and peptides, 4 fatty acid esters, 2 glycerophosphoethanolamines, 2 ceramides and 2 monoradylglycerols; among them, 12 metabolites were upregulated, and 15 were downregulated. The increased expression levels of glutamine, adenosine monophosphate and taurine were highly associated with PEMF stimulation in the PD model. The enrichment results of differentially abundant metabolite functional pathways showed that biological processes such as the mTOR signaling pathway, PI3K-Akt signaling pathway, and cAMP signaling pathway were significantly affected. Conclusion: PEMFs affected glutamine, adenosine monophosphate and taurine as well as their functional pathways in an in vitro model of PD. Further functional studies regarding the biological effect of these changes are required to evaluate the clinical efficacy and safety of PEMF treatment in PD.